High School Students’ Mathematical Problem-Solving Abilities: A Polya-Based Analysis - Febi Tasya Ramadhanti; Zainuddin Untu (Mandalika Mathematics and Educations Journal, 2026)
This study aims to analyze high school students' mathematical problem-solving abilities in exponential and logarithmic functions based on Polya's four stages of problem solving. This study employed a qualitative descriptive approach involving 72 tenth-grade students from a senior high school in Samarinda. Data were obtained through essay tests designed to reveal students' problem-solving processes and semi-structured interviews to strengthen the interpretation of students' work results. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results showed that students' problem-solving abilities varied across ability categories. High-ability students tended to plan, execute, and review the entire problem-solving process, although they did not always write down the initial information explicitly. Students with moderate abilities showed an initial understanding of the problem but had difficulty devising and carrying out a plan, which led to inadequately verified final results. Meanwhile, students with low abilities experienced obstacles from the problem comprehension stage, which led to failure in the subsequent stages. These findings emphasize the importance of strengthening conceptual understanding and practicing systematic problem-solving steps in mathematics learning.